If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 6 = 8(5p + 4) + -10(5 + 4p) Reorder the terms: 6 + p = 8(5p + 4) + -10(5 + 4p) Reorder the terms: 6 + p = 8(4 + 5p) + -10(5 + 4p) 6 + p = (4 * 8 + 5p * 8) + -10(5 + 4p) 6 + p = (32 + 40p) + -10(5 + 4p) 6 + p = 32 + 40p + (5 * -10 + 4p * -10) 6 + p = 32 + 40p + (-50 + -40p) Reorder the terms: 6 + p = 32 + -50 + 40p + -40p Combine like terms: 32 + -50 = -18 6 + p = -18 + 40p + -40p Combine like terms: 40p + -40p = 0 6 + p = -18 + 0 6 + p = -18 Solving 6 + p = -18 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + p = -18 + -6 Combine like terms: 6 + -6 = 0 0 + p = -18 + -6 p = -18 + -6 Combine like terms: -18 + -6 = -24 p = -24 Simplifying p = -24
| -7y+12=2y-6 | | 6/93.6= | | -x+1+9x-4+3x+10= | | 4(-4+5x)=-16 | | 16x^2-3x-1=0 | | 2n-5=8m+7 | | 6x-9=-13+4x | | 2(a^2+a+12)=0 | | 4x^2-8=64 | | 2x=4y+8 | | 2p^2-17p+13=0 | | h=4gf | | z+81.6=81.6 | | 7(x+3)=-2(x-5) | | x^4+28x^2-2304=0 | | 2m+8+6m=-8 | | 20(4+.25n)=5n | | 6r+1-4r-13= | | 7(6x+6)=-3(-5x+4) | | 3w-6+2w=2(3a+8) | | 3/4+1.5=2.7 | | 4x+12=2x+6 | | 12n^2+45n+27=0 | | 2x^2+3x+2=191 | | 3(w+4)-4(2w-2)=7 | | 2a^2+2a+24=0 | | 5p-9=7p+29 | | -4x-5=2x-10 | | 6a-3=2a-7 | | 2/3-6y=-5/6 | | 15+3(2x-4)-4x= | | 2t^2-t-6=0 |